Integration of lectin-glycan recognition systems and immune cell networks in CNS inflammation - Mendez Huergo, Santiago Patricio (2014)
Multiple sclerosis (MS) is a progressive degenerative disorder of the central nervous system (CNS), characterized by inflammation, demyelination and axonal loss. While the majority of MS patients experience relapsing-remitting symptoms followed by a secondary progressive phase, about 10–15% patients exhibit a primary progressive disease involving continuous progression from its onset. Here we review the role of lectin–glycan recognition systems, including those concerning siglecs, C-type lectins and galectins in the pathogenesis of MS and experimental autoimmune encephalomyelitis. Particularly, we will focus on the role of galectins in the fate of T cells, dendritic cells and CNS cell populations. Understanding the regulatory circuits governed by lectin–glycan interactions and their association with disease-associated cytokine networks will contribute to develop novel therapeutic strategies in MS.